Improving the conductive properties of printed electronics layers by treating paper substrates with corona discharge before screen printing - Kyrychok, Tetiana; Klymenko, Tetiana; Bardovskyi, Bohdan; Avdiakov, Yevhen (Eastern-European Journal of Enterprise Technologies, 2025)
This study’s object is the conductive layers of printed electronics based on graphene plastisol ink, applied by screen printing on glossy and matte paper substrates, pre-modified by corona discharge. The problem addressed is low adhesion and instability of conductive layers on paper substrates because of their roughness, porosity, and hydrophilicity. It was found that corona discharge treatment reduces the specific resistance of conductive tracks on matte paper by 25–30% compared to untreated samples; on glossy paper – by 8–12%. The best results were obtained at a power of 3000 W: for matte paper, the resistance of 1 mm wide tracks decreased from 1447.1 Ohm to 1035.6 Ohm, and for 5 mm tracks – from 184.0 Ohm to 161.1 Ohm. After testing, the increase in resistance in the M3000 samples averaged 2–5%, while in untreated counterparts it was up to 46%. Interpretation of the results revealed that the increase in surface energy and micro-roughness after corona treatment contributes to better wetting and fixation of graphene ink, the formation of a denser conductive layer, and a reduction in contact defects. A distinctive feature is the confirmed stability of electrical characteristics after thermal cycles and a decrease in the proportion of complete failures in pre-treated glossy paper samples. Additionally, a reduction in measurement scatter and improved print reproducibility for narrow tracks (1–2 mm) on matte paper after 3000 W corona treatment was noted. The practical significance of the results is the possibility of using corona discharge treatment in the production of flexible printed electronics on paper media, especially for miniature elements with high requirements for conductivity and wear resistance. The method is effective in mass roll-to-roll (R2R) production, compatible with thin substrates, and does not require complex integration into the technological process